Britain in Egypt : Egyptian Nationalism and Imperial Strategy, 1919-1931. - Gifford, Jayne (I.B. Tauris & Company, Limited, 2019)
"Egypt under the British tends to be looked at now through a post-Suez lens - an inevitable disaster and the last puncturing of a doomed empire. But in fact Egypt for many years was the cornerstone of British success across the Middle East and North Africa. This image of empire was shattered after the First World War by the development of nationalism in Egypt - the foundation and growth of the nationalist Wafd party led by Saad Zaghlul and the creation of the Muslim Brotherhood in 1928. Throughout this period Britain continued to control the Nile Valley - under Field Marshal Allenby and then George Lloyd - through a policy of deliberate containment of nationalism and a slow relinquishing of powers (culminating in the Anglo-Egypt Treaty of 1936). This book will be the first to study that process in the Nile Valley in any great detail and contains previously unpublished primary sources."--